Transformasi e-HRM (Electronic Human Resource Management) dalam Pengembangan Kualitas SDM (Sumber Daya Manusia) Berbasis Teknologi Informasi Terhadap Kinerja Karyawan - Sumaryono, Sumaryono (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
The Human Resources Information System is a subsystem of HRM-e (Electronic Human Resources Management), which is a special form of information system established for HRM needs. The HRM system aims to improve the business processes of the HR department and to achieve more efficient results in business processes. HRM-e is designed for personnel outside the HR department and employees and managers of organizations. HRM-e allows HR applications to be used by organizational employees without any place and time restrictions outside the organization. The HRM system is not a technology itself, but an integration of HR processes with information and communication technology. Based on this point of view, HRM-e is viewed. Web-based HRM and IT (Information Technology)-based HRM practices can be considered as developments and stages that facilitate the functioning of HRM information systems. The application of HRM-e to HRM practices in organizations can be in the form of: 1. E-Learning; 2. Performance Management System; 3. E-Compensation System; 4. E-Job Evaluation and E-Renumeration System; 5. Satisfaction; and 6. Employee Performance. This e-HRM practice can increase effectiveness and efficiency for the organization.